(untitled) (Journal of Informatics and Mathematical Sciences, 2009)
Functional, integral and differential equations of transformed characteristic functions are very strong analytical tools for establishing characterizations of probability distributions. The present paper establishes a characterization of the distribution of a fundamental stochastic multiplicative model by making use of an integral equation based on three well known transformed characteristic functions.